واقع وافاق الطاقات المتجددة في الجزائر - ربيحة, جغبالة; مسعودة, جغبالة (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة الى ابراز قضية استخدام الطاقات المتجددة كبديل مستقبلي للطاقات الأحفورية لاجابياتها وميزاتها، كونها طاقات نظيفة وصديقة للبيئة، بالإضافة إلى انها غير ناضبة وموجودة بصورة دائمة ومستمرة في الطبيعة، كما انها تخفض معدلات استخدام الطاقات الناضبة بغض النظر عن تكلفتها. والجزائر كغيرها من الدول ابدت اهتماما بالغا بالطاقات المتجددة، كونها بلد ربعي يعتمد على الطاقات الأحفورية التي بدأت حقولها بالنضوب، لهذا وضعت الجزائر مجموعة من الاستراتيجيات لاستغلال مثل هذه الموارد من خلال إطلاق برنامج طموح على المدى البعيد الصادر في 2014 إلى غاية 2030، كما انها اولت أكبر قدر من الأهمية في استغلال كل من الطاقة الشمسية وطاقة الرياح نظرا للإمكانيات الهائلة التي تتمتع بما في كلا من المصدرين وخاصة في منطقة الجنوب This study aims to highlight the issue of using renewable energies as a future being clean and alternative to fossil energies for its advantages and advantages in addition to that it is inexhaustible and is environmentally friendly energies and it also reduces the rates of using permanently and continuously present in nature depleted energies regardless of its cost. has shown great interest in renewable energies, like other countries. And Algeria as it is a rentier country that depends on fossil energies whose fields have begun to Algeria has developed a set of strategies to exploit such deplete. For this reason, by launching an ambitious long-term program issued in 2014 until 2030. It resources has also given the greatest importance to the exploitation of both solar and wind energy especially in the south. due to the huge potential, it enjoys in both sources
Keywords: الطاقة،الطاقات المتجددة، الجزائر